Purifikasi Kewenangan Pengadilan Niaga dalam Menangani Perkara Kepailitan/PKPU - Lucky Omega Hasan (CV. Syntax Corporation Indonesia, 2021)
The presence of contemporary insolvency instruments apparently not only touches on sectors related to the legal relationship of receivable debt, but also has begun to shift to legal relationships that were originally or originally not from receivable debt, but began from criminal acts. This paper uses normative law research that examines legal norms seen from historical aspects, principles and theories of legal law, legal systematics, vertical and horizontal synchronization. Then obtained the results of ilimiah dialectics, studies on general bail and criminal bail are many choices of legal studies both in the form of journal writing, thesis even up to dissertation. Various opinions, diverse perspectives only produce polemics which should come first whether public sita or criminal sita do not find a bright spot or meeting point. Therefore, a firm and solutive middle ground must be taken by purifying the authority of the Commercial Court based on the reason of justification using the approach of historical and theoretical aspects. Expecting political will against amendments to Law No. 37 of 2004 on Insolvency is a long and uncertain waiting period, therefore, this polemic must be resolved by the scheme of the Supreme Court of the Republic of Indonesia must dare to issue legal products SEMA (Circular Letter of the Supreme Court) that purify the position and authority of the Commercial Court that only accepts bankruptcy applications or PKPU derived from treaty law, laws or court rulings regarding liability for damages due to unlawful acts. Based on this, so that all cases of criminal dimension can no longer be resolved through commercial court channels that cause a new polemic, namely disputes between public courts and criminal sita